The Life Philosophy of the Banjarese as a Value Education in Learning History - Dewicca Fatma Nadilla (Yupa: Historical Studies Journal, 2017)
Banjar people known as nomads and merchants in his life is famous for the principle that formed the character of the Banjar. Through the values contained in the philosophy/life principle of the Banjar people who can then be integrated into the world of education, one of which is historical education. The meaning and value of local wisdom existing in the community has a goal to increase learners to be able to develop their attributes derived from wisdom and local history of society, possessed the skill in understanding the society in the life of the process and possessing the characteristics and attitudes that are in line with the value of local wisdom. Amid the onslaught of technology and practicality of life offered, later emerged an approach that tried to highlight the local wisdom owned by the region, especially South Kalimantan. Therefore, the purpose of this paper is to introduce the value of the urban life of Banjar philosophy and its integration in learning history as a form of cultural endurance. The method used in this writing that is with a qualitative approach and data collection is done by library study by collecting the relevant literature with this paper.